2021
DOI: 10.5888/pcd18.210062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neighborhood Ethnic Density and Psychosocial Factors on Colorectal Cancer Screening Behavior Among Asian American Adults, Greater Philadelphia and New Jersey, United States, 2014–2019

Abstract: What is already known on this topic?Neighborhood ethnic density and composition may play a critical role in individual health behaviors, attitudes, and outcomes related to colorectal cancer (CRC).What is added by this report?Few studies have been conducted to understand whether CRC screening behavior is affected by ethnic density in Asian American neighborhoods. We examined how the neighborhood environment, specifically ethnic composition and the interplay with psychosocial factors, influences CRC screening am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested several barriers for Asian Americans to screening cancers, including language barriers 46 and neighborhood environment. 47 Further intervention programs addressing these barriers should be implemented to mitigate health disparities among Asian Americans. Culturally tailored health education workshops, individual shared decision-making process with physicians, and easily accessed medical translation services should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested several barriers for Asian Americans to screening cancers, including language barriers 46 and neighborhood environment. 47 Further intervention programs addressing these barriers should be implemented to mitigate health disparities among Asian Americans. Culturally tailored health education workshops, individual shared decision-making process with physicians, and easily accessed medical translation services should be provided.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary treatment (MDT) means that the medical staff coming from different subjects provide patients with independent suggestions about diagnosis and treatment, implement efficient medical services, and formulate the best treatment plans with individual differences according to patients' condition based on the support of data system. In 2016, the National Family Planning Commission in China pointed out that the oncology department should actively implement the treatment mode of single disease and multiple subjects [ 11 ]. However, the plan of nutrition support team under the MDT mode has not been implemented due to the practical factors.…”
Section: Introductionmentioning
confidence: 99%